Thoracic ultrasound for diagnosing pneumopathies in neotropical primates - Martins, Jéssica Amancio; de Souza Balbueno, Melina Castilho; Málaga, Soraya Kezam; da Costa, Leonardo Dourado; de Paula Coelho, Cidéli (Frontiers in Veterinary Science, 2024)
Lung ultrasound can be useful for the early diagnosis and treatment of respiratory complications. The combination of air and soft tissue confirms imaging artefacts that can contribute to differentiation between healthy and deteriorated lung tissue. Although non-human primates are often chosen as research models due to their anatomical and physiological similarity to humans, there is a lack of data on the use of lung ultrasound in these individuals. The aim of this study was to evaluate the contribution of ultrasound examinations of the thoracic region of Callithrix sp. for diagnosing pneumopathy. Parameters were obtained from 166 new world non-human primates of both sexes, aged between 1 and 15 years and weighing between 128 g and 680 g kept under human care at the Mucky Project in Itu, São Paulo. Thoracic ultrasound examinations were carried out using a LOGIQe—R7 device (GE, United States), with a 10–22 MHz linear transducer, at four points on the left and right antimeres. Among these 166 individuals, 72 had some kind of pulmonary alteration. Forty-one of the animals with pulmonary alterations diagnosed on ultrasound died and underwent necropsy. Histopathological examination showed that in half of the samples the lung tissue was compatible with some form of pneumopathy. Considering these cases, the pulmonary alterations diagnosed through thoracic ultrasound examination in Callithrix sp. can be correlated with the occurrence of pneumopathy, which is often asymptomatic. Lung ultrasound is an important tool for use in clinics to detect and monitor respiratory diseases and can save lives by enabling early treatment.